Increasing Urban Flood Challenges: Spatial Analysis of the 2024 Flood in Rajabasa, Bandar Lampung, Indonesia - Rohman, Arif; Septiana, Trisya; Despa, Dikpride (PT Penjaminan Infrastruktur Indonesia (Persero), 2024)
This study explores the spatial analysis of flood-prone areas in Rajabasa by utilizing Digital Elevation Model data from DEMNAS and high-resolution aerial photographs obtained via commercial drones. The research aims to understand the region’s flood dynamics and watershed characteristics. The elongated shape of the Rajabasa basin, with a calculated circularity ratio (Rc) of 0.19, indicates that runoff follows the existing stream network, resulting in gradual and prolonged flood events. Field surveys were conducted to validate land cover data, revealing that the majority of the area was residential and classified under Hydrology Soil Group (HSG) D, leading to high Curve Number (CN) values between 88 and 93. These values suggest that nearly all rainfall converts to runoff, exacerbating flooding conditions. Effective flood management strategies were proposed by focusing on areas with the highest CN values and integrating long-term land improvement with short-term flood control infrastructure. The study also highlights the importance of preserving natural drainage lines, which are often overlooked, for enhancing flood mitigation, educating residents about floodplain management, and implementing proper land use regulations. The findings underscore the necessity of combining spatial analysis, high-resolution data, and targeted flood management strategies to mitigate flood risks in Rajabasa and similar flood-prone areas.